Pengaruh Pelaksanaan Supervisi Akademik Pengawas Sekolah Dan Supervisi Kepala Sekolah Terhadap Kinerja Guru SMK Negeri Di Kabupaten Majene - Ramadhan, Ahmad (Journal of Educational Science and Technology (EST), 2017)
This research aims at examining the implementation of academic supervison by schoolsâ supervisors, supervision by the principals and teachersâ performances, the influence of the implementation of academic supervision by schoolsâ supervisors toward teachersâ performance, the influence of supervision by principal toward teachersâ performance and the influence of the implementation of academic supervision by supervisors and the supervision by the principals simultaneously toward teachersâ performance at SMKN in Majene district. Type ex post facto research, with 210 teachers of civil servants as a population in the sample of 138 teachers determined by proportional random sampling technique. The instruments used were questionnaires with teacher respondents. Instrument development begins content validation, grains and instruments. Analysis using descriptive analysis and infrensial analysis. The results of descriptive analysis indicate that the implementation of supervision of school supervisor supervision is not done well and categorized low, supervision of principal executed well and categorized high and performance of teacher executed well and categorized high. The results of inferential analysis using linear regression indicate that; (1) the implementation of academic supervision by schoolsâ supervisors give significant influence toward teachersâ performances, (2) supervision by the principals significant influence toward teachersâ performances, (3) the implementation of academic supervision by schoolsâ supervisors and supervision by the principals collectively give significant influence toward teachersâ performance.Â